Customers#x2019; Perception towards Online Shopping in Jordan (Global Journal of Management and Business Research, 2021)
Online shopping is gaining popularity across the globe, thanks to the speedily advancing and easily accessible internet that allowed online marts to transcend the traditional methods of trading. A highly challenging lifestyle is convincing consumers to adopt online shopping as a substitute to traditional retailing to save time and money. Therefore, this study was conducted to examine the perception of customers towards online shopping in Jordan. The research conducted an online survey of 400 customers who bought online products. Trust, convenience, price, customer service, product varieties, and website design were used as the variables on which the customers#x2019; perception towards online shopping was examined.
Keywords: customer; online shopping; regression; jordan